PEMETAAN PEMASARAN ABON IKAN TUNA (Thunnus Sp) (Suatu Kasus pada Usaha Karya Mandiri “ Bu Bedah” Desa Muara Kecamatan Wanasalam - Kabupaten Lebak - Banten) - Bukhari, Ahmad; Krisdianto, Nanang (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
This research is to describe the marketing mapping abon of tuna fish by using quantitative mapping, market mapping, price mapping, and traffic mapping. This study used survey method to determine the location of the intentionally (purposive) that is in Business Karya Mandiri